QT prolongation predicts short-term mortality independent of comorbidity. Issue 8 (8th April 2019) - Gibbs, Charlotte; Thalamus, Jacob; Kristoffersen, Doris Tove; Svendsen, Martin Veel; Holla, Øystein L; Heldal, Kristian; Haugaa, Kristina H; Hysing, Jan
Abstract: Aims: A prolonged corrected QT interval (QTc) ≥500 ms is associated with high all-cause mortality in hospitalized patients. We aimed to explore any difference in short- and long-term mortality in patients with QTc ≥500 ms compared with patients with QTc <500 ms after adjustment for comorbidity and main diagnosis. Methods and results: Patients with QTc ≥500 ms who were hospitalized at Telemark Hospital Trust, Norway between January 2007 and April 2014 were identified. Thirty-day and 3-year all-cause mortality in 980 patients with QTc ≥500 ms were compared with 980 patients with QTc <500 ms, matched for age and sex and adjusting for Charlson comorbidity index (CCI), previous admissions, and main diagnoses. QTc ≥500 ms was associated with increased 30-day all-cause mortality [hazard ratio (HR) 1.90, 95% confidence interval (CI) 1.38–2.62; P < 0.001]. There was no significant difference in mortality between patients with QTc ≥500 ms and patients with QTc <500 ms who died between 30 days and 3 years; 32% vs. 29%, P = 0.20. Graded CCI was associated with increased 3-year all-cause mortality (CCI 1–2: HR 1.62, 95% CI 1.34–1.96; P < 0.001; CCI 3–4: HR 2.50, 95% CI 1.95–3.21; P < 0.001; CCI ≥5: HR 3.76, 95% CI 2.85–4.96; P < 0.001) but was not associated with 30-day all-cause mortality. Conclusion: QTc ≥500 ms is a powerful predictor of short-term mortality overruling comorbidities. QTc ≥500 ms also predicted long-term mortality, but this effect was mainly caused by the increased short-term mortality. For long-term mortality, comorbidity was more important.